Can Financialization Save Nature? The Case of Endangered Species* - Arjaliès, Diane‐Laure; Gibassier, Delphine (Contemporary Accounting Research, 2023)
ABSTRACT The current biodiversity loss is dramatic. Over the past 50 years, more than 68% of the mammals, birds, amphibians, reptiles, and fish on Earth have disappeared, putting the planet's survival and its inhabitants—including human beings—at risk. Financialization, or the transformation of nature into financial assets, is increasingly proposed as a solution to the biodiversity crisis. Proponents of financialization believe that assigning a monetary value to nature will incentivize human beings to protect habitats and their species. This article offers a four‐mechanism model of nature's financialization, explaining why it is virtually impossible to financialize nature. We collected data through a unique two‐stage data collection process, including a single case study and additional interviews with conservationists and conservation finance specialists. We analyzed the development of a calculative device, the “Index,” designed to assess the impact of conservation efforts on the survival of endangered species. Conservationists hoped to use the Index to calculate the financial return of a conservation impact bond, a financial instrument designed to finance conservation projects. However, they did not achieve their goal. We discuss the implications for the financialization and conservation literature and the role of accounting therein. We notably question previous accounts of financialization, including the need for financial numbers or financial actors. We ultimately show that a financialization project can transform practices toward financialization, even if the financialization process is not complete.